Impact of groundwater table variation in 2D and 3D seepage and slope stability analyses - Kong, Ming Xuan (Nanyang Technological University, 2023)
The issue of rainfall-induced landslides has become more severe due to the increasing occurrence of intense precipitation caused by global climate warming. This is an exclusively dire issue for tropical nations that receive abundant rainfalls such as Singapore. As residual soils in Singapore often exist in unsaturated state, infiltration of rainwater decreases the suction and shear strength in the soil, which could lead to slope failures. Hence, it is important to incorporate unsaturated soil mechanics for the slope stability analyses to establish a more precise identification of critical slopes. While it is typical to use two-dimensional (2D) numerical analyses to evaluate the stability of a single slope, regional analyses using three-dimensional (3D) numerical models can provide a more comprehensive and precise assessment of slope stability across a larger study area that includes multiple slopes. Groundwater table plays an important role in determining the stability of a slope as it is associated with the water flow in the soil. During rainfall, the variation in groundwater table influences the infiltration of rainwater into the soil. The objective of this study is to investigate the stability of residual soil slopes within a selected Jurong Formation zone in Singapore under the effects of variations in groundwater table with respect to rainfall. Unsaturated soil properties were obtained from a soil database developed specifically for Singapore and incorporated into the numerical models. To assess the slope stability under maximum daily rainfall, 3D regional analyses were conducted using GEOtop and Scoops3D. GEOtop is a widely used open-source software that simulates water movement and heat transfer in soils, allowing for comprehensive analysis of soil-water interactions in complex terrain. Scoops3D, on the other hand, is a commercial software that specializes in 3D slope stability analysis, taking into account various factors such as soil properties, groundwater conditions, and rainfall patterns. The results from the 3D regional analyses were compared with those from 2D numerical analyses conducted in GeoStudio, using SEEP/W for seepage analysis and SLOPE/W for slope stability analysis, both of which are modules within GeoStudio software. The comparison was based on groundwater table and pore-water pressure profiles, as well as changes in the Factor of Safety (FS) values. The groundwater table in 2D analyses was modelled using different methods based on the 3D slope data. Results of the comparison suggest that the 3D analyses did not consistently produce higher pore-water pressure distributions and Factor of Safety (FS) compared to the 2D analyses. Therefore, it can be concluded that 3D regional analyses do not necessarily provide more conservative results, as 2D analyses can also produce conservative estimates at times. It is vital to plot pore-water pressure and groundwater table profiles, as well as generate the flow direction information from slope model to ensure a more reliable results in 3D analyses.